2009
DOI: 10.3402/ijch.v68i1.18297
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and maternal age distribution of abdominal wall defects in Norway and Arkhangelskaja Oblast in Russia

Abstract: Objectives. To determine the foetal incidence of isolated anterior abdominal wall defects (gastroschisis and omphalocele) in the Arkhangelskaja Oblast (AO) in Russia and in Norway, as well as to study the maternal -age distribution of these defects. Study Design. A register -based incidence study. Methods. All registered foetuses and newborns with at least weeks of gestation in the populations of AO (4,59) and Norway (9,708) were included. The data covered the period 995-004 in AO and 999-00 in Norway and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 15 publications
0
8
2
2
Order By: Relevance
“…AO has had a system for collecting data about birth defects and perinatal and infant mortality since 1995, and has participated in a monitoring program that includes compulsory notification and registration of congenital defects (12). Additional details have been reported (13, 15, 21).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…AO has had a system for collecting data about birth defects and perinatal and infant mortality since 1995, and has participated in a monitoring program that includes compulsory notification and registration of congenital defects (12). Additional details have been reported (13, 15, 21).…”
Section: Methodsmentioning
confidence: 99%
“…Their center of medical genetics registered spontaneous abortuses with defects. More details about the registration of newborns and medical abortuses with defects have been previously reported (13, 15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of gastroschisis in recent years has a remarkably increasing trend in some areas but has remained unchanged in other areas; in gen-eral, gastroschisis prevalence has increased significantly since the 1970s (Baerg et al, 2003;Reid et al, 2003;Arnold, 2004;Alvarez and Burd, 2007). Additionally, the relevant studies that mainly focused on the risk factors of gastroschisis incidence, such as race, age, smoking, and drug use of the mothers, consistently showed that the increasing gastroschisis prevalence may be associated with the change in the mother's age (Hougland et al, 2005;Petrova and Vaktskjold, 2009;Feldkamp and Botto, 2008;Forrester and Merz, 2006;Loane et al, 2007;Nichols et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…They focus on prevalence rates and time trends, but it is difficult to conduct a systematic scientific investigation (e.g. of case control design) of risk factors due to a lack of information in such registries [12,13]. In addition, there is no experience in Russia at the local or national level of linking such data with birth registries.…”
Section: Introductionmentioning
confidence: 99%